1997
DOI: 10.1523/jneurosci.17-19-07490.1997
|View full text |Cite
|
Sign up to set email alerts
|

Vector Averaging for Smooth Pursuit Eye Movements Initiated by Two Moving Targets in Monkeys

Abstract: The visual input for pursuit eye movements is represented in the cerebral cortex as the distributed activity of neurons that are tuned for both the direction and speed of target motion. To probe how the motor system uses this distributed code to compute a command for smooth eye movements, we have recorded the initiation of pursuit for 150 msec presentations of two spots moving at different speeds and/or in different directions. With equal probability, one of the two spots continued to move at the same speed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
102
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 33 publications
16
102
2
Order By: Relevance
“…In a perceptual discrimination task, Salzman and Newsome (1994) found evidence favoring a winnertake-all readout of MT activity. In a second approach, Groh et al (1997) microstimulated MT during the initiation phase of smooth pursuit eye movements and found clear evidence of a vectoraveraging readout of MT, a conclusion that was supported by subsequent behavioral studies of pursuit initiation (Lisberger and Ferrera, 1997).…”
Section: Resultsmentioning
confidence: 59%
“…In a perceptual discrimination task, Salzman and Newsome (1994) found evidence favoring a winnertake-all readout of MT activity. In a second approach, Groh et al (1997) microstimulated MT during the initiation phase of smooth pursuit eye movements and found clear evidence of a vectoraveraging readout of MT, a conclusion that was supported by subsequent behavioral studies of pursuit initiation (Lisberger and Ferrera, 1997).…”
Section: Resultsmentioning
confidence: 59%
“…Most of these studies used dots (either single spot or random-dots flowfields) moving in different directions across different parts of the visual field. Lisberger and Ferrera (1997) assumed that "the pursuit system uses the same computation to combine information from the two spatial locations [we used] as it does for a single location" (page 7500). The present study indicates that a vector combination strategy is used to recover the 2D direction of object motion.…”
Section: Motion Integration For 2d Trackingmentioning
confidence: 99%
“…A wide variety of studies have found evidence for vector averaging in the saccadic system using both physiological and behavioral techniques (Robinson and Fuchs, 1969;Robinson, 1972;Becker and Jurgens, 1979;Schiller et al, 1979;Findlay, 1982;Schiller and Sandell, 1983;du Lac and Knudsen, 1987;Lee et al, 1988;du Lac, 1989;van Opstal and van Gisbergen, 1990;McIlwain, 1991;Glimcher, 1993). Recently, Lisberger and Ferrera (1996) have examined the pursuit responses of monkeys when two moving visual targets are presented. They found evidence for both vector averaging (Lisberger and Ferrera, 1996) and winner-take-all mechanisms (Ferrera and Lisberger, 1995) depending on the conditions of the task.…”
Section: Overview Of Microstimulation Effectsmentioning
confidence: 99%
“…Recently, Lisberger and Ferrera (1996) have examined the pursuit responses of monkeys when two moving visual targets are presented. They found evidence for both vector averaging (Lisberger and Ferrera, 1996) and winner-take-all mechanisms (Ferrera and Lisberger, 1995) depending on the conditions of the task.…”
Section: Overview Of Microstimulation Effectsmentioning
confidence: 99%